الاتجاهات الحديثة في تطبيقات البحوث الكيفية بدراسات الإعلام وتكنولوجيا الاتصال - مجدى, الداغر (جامعة الوادي - University of Eloued, 2022)
تستهدف الدراسة التعرف على المفاهيم والمصطلحات المصاحبة لتطبيقات البحوث الكيفية بالدراسات الإعلام، وكذلك نوعية المناهج والأدوات البحثية المصاحبة للدراسات والبحوث الإعلامية، كما تهدف الى رصد التطبيقات الإلكترونية المستخدمة في البحوث الكيفية في الدراسات الإعلامية، حيث يقوم موضوع الدراسة الحالية حول "الاتجاهات الحديثة في تطبيقات البحوث الكيفية" في إطار المدارس الأكاديمية المختلفة، وذلك من خلال توصيف أهم الفروع البحثية التي استندت عليها البحوث الكيفية في السنوات الأخيرة، وأظهرت نتائج الدراسة أن البحث الكيفي هو أكثر اهتماما بفهم الظاهرة الاجتماعية من منظور المشاركين أنفسهم، ومن خلال معايشة الباحث لحياة المشاركين العادية، حيث أن الأفعال الإنسانية وآراء الأفراد ومعتقداتهم تتأثر بالمواقف والبيئة التي تحدث فيها، كما كشفت النتائج وجود صعوبات في تطبيق البحوث الكيفية في الإعلام الجديد، ويظهر ذلك من خلال قلة المراجع، البحوث والدراسات السابقة، والتوثيق، وصعوبة تحديد فئات البحث، والمفاهيم وصعوبة قياس تأثير الإعلام الجديد على الجمهور. Summary Recent trends in qualitative research applications in media studies and communication technology The study aims to identify the concepts and terms associated with the applications of qualitative research in media studies, as well as the quality of curricula and research tools accompanying media studies and research, and also aims to monitor the electronic applications used in qualitative research in media studies, where the subject of the current study is about “modern trends in qualitative research applications.” Within the framework of the various academic schools, by describing the most important research branches on which qualitative research has been based in recent years The results of the study showed that qualitative research is more interested in understanding the social phenomenon from the perspective of the participants themselves, and through the researcher's experience of the participants' normal lives, as human actions and individuals' opinions and beliefs are affected by the situations and environment in which they occur, and the results revealed that there are difficulties in applying qualitative research in the media. What is new, and this is shown by the lack of references, previous research and studies, documentation, the difficulty of defining research categories, concepts and the difficulty of measuring the impact of the new media on the public.
Recent trends in qualitative research applications Media studies and communication technology
مقال
Keywords: البحوث الكيفية ، دراسات الاعلام والاتصال ، الاتجاهات الحديثة; media and communication studies, qualitative research , new trends